Virtual Reality in Creative Education: An Experimental Study on Engagement and Concept Mastery - Najwa Syarofa; Ali Khan; Kiran Iqbal (Journal of Loomingulisus ja Innovatsioon, 2025)
The integration of immersive technologies into educational settings has introduced new possibilities for enhancing creativity, engagement, and understanding of abstract concepts. Virtual Reality (VR), as one of the most advanced digital tools, offers interactive three-dimensional environments that can transform traditional teaching approaches. This study aims to examine the effects of VR-based learning on student engagement and concept mastery within creative education courses. An experimental research design was implemented with 80 undergraduate students randomly assigned to an experimental group using VR applications and a control group using conventional multimedia. The intervention focused on design-thinking modules over a six-week period. Data were collected using engagement observation checklists, concept mastery tests, and post-intervention questionnaires, and analyzed through descriptive and inferential statistics. Results revealed that the experimental group demonstrated significantly higher engagement levels and achieved better scores in conceptual understanding than the control group. Students reported that VR facilitated exploration, provided a more stimulating learning environment, and encouraged active participation in problem-solving activities.